Aplicação do adesivo poliuretano derivado do óleo de mamona na obtenção de painéis de madeira colados lateralmente - Mölleken, Richard Eduard (2017)
Due to concerns about the environment and technological advances in the chemical and forestry area, technological alternatives are sought for the development of new products. The Edge Glued Panels, EGP, enable the optimization of the use of forest resources and are composed of wood joints joined by adhesive bonding on the sides and tops and evaluated according to EN-13353.These panels can be manufactured with vinyl polyacetate adhesive, PVAc and emulsion polymer isocyanate, epoxy, which are derived from petroleum. The polyurethane adhesive derived from castor oil is an alternative to replace these adhesives, since it is a material that has no solvent, is biodegradable and derived from renewable raw material. The objective of this work was to evaluate the polyurethane adhesive derived from castor oil for the production of Edge Glued Panels. The Pinus taeda and Tectona grandis species were used for bonding with the polyurethane adhesive and compared with the PVAc and EPI adhesives, with pressings at different times, proportions of polyol and prepolymer and different weights subjected to conditioning according to standard EN-13353 for the evaluation of the bonding quality of solid wood panels. All the specimens were evaluated by the shear test on the glue line. It was observed that the time most suitable to produce EGP with the PU adhesive for Pinus taeda was 4 hours, with a ratio of 1: 0.7 and weight of 180 g / m² and for Tectona grandis species it was 4 hours, with a ratio of 1: 0.7 and 120 g / m², where all values met the standard for laterally bonded panels EN-13353, and were higher than the values obtained with PVAc and EPI adhesives.